Age‐related changes in hippocampal‐dependent synaptic plasticity and memory mediated by p75 neurotrophin receptor. Issue 2 (15th January 2021) - Wong, Lik‐Wei; Chong, Yee Song; Lin, Wei; Kisiswa, Lilian; Sim, Eunice; Ibáñez, Carlos F.; Sajikumar, Sreedharan
Abstract: The plasticity mechanisms in the nervous system that are important for learning and memory are greatly impacted during aging. Notably, hippocampal‐dependent long‐term plasticity and its associative plasticity, such as synaptic tagging and capture (STC), show considerable age‐related decline. The p75 neurotrophin receptor (p75 NTR ) is a negative regulator of structural and functional plasticity in the brain and thus represents a potential candidate to mediate age‐related alterations. However, the mechanisms by which p75 NTR affects synaptic plasticity of aged neuronal networks and ultimately contribute to deficits in cognitive function have not been well characterized. Here, we report that mutant mice lacking the p75 NTR were resistant to age‐associated changes in long‐term plasticity, associative plasticity, and associative memory. Our study shows that p75 NTR is responsible for age‐dependent disruption of hippocampal homeostatic plasticity by modulating several signaling pathways, including BDNF, MAPK, Arc, and RhoA‐ROCK2‐LIMK1‐cofilin. p75 NTR may thus represent an important therapeutic target for limiting the age‐related memory and cognitive function deficits. Abstract : This cartoon depicts the signaling pathway by p75NTR in mediating synaptic plasticity changes in aging. Aging increases proBDNF without affecting mature BDNF. ProBDNF has been implicated in facilitating LTD. Aging also modulates MAPK pathway by upregulating p38 activity while downregulating ERK1/2 activity. Both p38 and ERK1/2 pathways are important in regulating Arc gene transcription. Aging decreases Arc protein, thus affecting the maintenance of LTP and LTM consolidation through regulation of actin dynamics. In addition, aging increases RhoA level leading to an increase in ROCK2 activity. This reduces both LIMK1 and cofilin phosphorylation. Modulation of cofilin activity is essential for the reorganization of the actin cytoskeleton and influences synaptic plasticity. As a whole, p75NTR is responsible for the age‐mediated disruption of hippocampal homeostatic long‐term plasticity by modulating several signaling pathways, including BDNF, MAPK, Arc, and RhoA‐ROCK2‐LIMK1‐cofilin, leading to deficits in STC and associative memory. Red arrow indicates increases. Green arrow indicates decreases. Orange equals sign indicates no change.